Interculturality, interaction and language learning insights from tandem partnerships - Woodin, Jane (Routledge studies in language and intercultural communication, 2018)
"This book opens up new lines of debate in language learning and intercultural communication through an investigation of tandem language learning (a method of language learning based on mutual language exchange between native speakers and learners of each other's language) in connection with intercultural learning and identity construction. Through an empirical study of face-to-face tandem conversations, Jane Woodin provides compelling evidence for the re-definition of the tandem partnership beyond the traditional native speaker-non-native speaker (NS-NNS) paradigm. By analyzing conversation shapes, learner identification of self and other and interactants' own focus on culture, this book reveals how interactants themselves address the complexities of language, learning, ownership and meaning. The book also questions the prevalence of models of intercultural competence which describe the competence of the individual, with little recognition of the role of the relationship or interaction. Woodin considers the broader applicability of the tandem framework of autonomy and reciprocity, and suggests new directions for further research on tandem learning."--